Aging effect of AlF3 coatings for 193 nm lithography. (1st February 2018) - Zhao, Jia; Wang, Lin; Zhang, Weili; Yi, Kui; Shao, Jianda
Highlights: Studying aging effect of AlF3 coating material by resistive heating method from more aspects. Different characterization methods were combined to analyze the mechanism of aging effect. Measured roughness values combined with spectra calculation to talk about scattering and absorption. Abstract: As important part of components for 193 nm lithography, AlF3 coatings deposited by resistive heating method acquire advantages like lower optical loss and higher laser damage threshold, but they also possess some disadvantages like worse stability, which is what aging effect focuses on. AlF3 single-layer coatings were deposited; optical property, surface morphology and roughness, and composition were characterized in different periods. Owing to aging effect, refractive index and extinction coefficient increased; larger and larger roughness caused more and more scattering loss, which was in the same order with absorption at 193.4 nm and part of optical loss; from composition analysis, proportional substitution of AlF3 by alumina may account for changes in refractive index as well as absorption.